Sequential Deposition of Organic Films with Eco-Compatible Solvents Improves Performance and Enables Over 12%-Efficiency Nonfullerene Solar Cells. - Ye,L; Xiong,Y; Chen,Z; Zhang,Q; Fei,Z; Henry,R; Heeney,M; O'Connor,BT; You,W; Ade,H (Adv Mater, 2019)
Casting of a donor:acceptor bulk-heterojunction structure from a single ink has been the predominant fabrication method of organic photovoltaics (OPVs). Despite the success of such bulk heterojunctions, the task ofcontrolling the microstructure in a single casting process has been arduous and alternative approaches are desired. To achieve OPVs with a desirable microstructure, a facile and eco-compatible sequential deposition approach is demonstrated for polymer/small-molecule pairs. Using a nominally amorphous polymer as the model material, the profound influence of casting solvent is shown on the molecular ordering of the film, and thus the device performance and mesoscale morphology of sequentially deposited OPVs can be tuned. Static and in situ X-ray scattering indicate that applying (R)-(+)-limonene is able to greatly promote the molecular order of weakly crystalline polymers and form the largest domain spacing exclusively, which correlates well with the best efficiency of 12.5% in sequentially deposited devices. The sequentially cast device generally outperforms its control device based on traditional single-ink bulk-heterojunction structure. More crucially, a simple polymer:solvent interaction parameter χ is positively correlated with domain spacing in these sequentially deposited devices. These findings shed light on innovative approaches to rationally create environmentally friendly and highly efficient electronics.